2016
DOI: 10.17795/zjrms-2664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Stresses on Growth Pattern, Biofilm Formation and Biochemical Characteristics of Mycobacterium marinum CCUG20998

Abstract: Background: Mycobacterium marinum is a ubiquitous, slow-growing nontuberclosis Mycobacterium (NTM), it can causes disseminated granulomatous infections in fish. Outbreaks in fisheries can be financially devastating and can also increase the chance of human exposure. Objectives: The aim of this work was evaluating the effects of some environmental stresses on M. marinum CCUG 20998. Methods: In this descriptive-analytic study M. marinum CCUG 20998 was subjected to different conditions of environmental stresses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Al-Nabulsi et al [ 20 ] showed a tendency for antibiotic resistance to increase with decreasing pH. In contrast, Faezi-Ghasemi and Kazemi [ 56 ] have found that L. monocytogenes exposed to pH 5 or osmotic stress (7% NaCl) was more sensitive to tetracycline, rifampicin, gentamicin, penicillin, ampicillin, trimethoprim-sulfamethoxazole and chloramphenicol. In our study, the effect of osmotic and acid stress on MIC values depended on the antibiotic used and strain.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Nabulsi et al [ 20 ] showed a tendency for antibiotic resistance to increase with decreasing pH. In contrast, Faezi-Ghasemi and Kazemi [ 56 ] have found that L. monocytogenes exposed to pH 5 or osmotic stress (7% NaCl) was more sensitive to tetracycline, rifampicin, gentamicin, penicillin, ampicillin, trimethoprim-sulfamethoxazole and chloramphenicol. In our study, the effect of osmotic and acid stress on MIC values depended on the antibiotic used and strain.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that food strains resistant to ciprofloxacin, nitrofurantoin and erythromycin were significantly more resistant to acidic stress than susceptible strains [34]. In contrast, Faezi-Ghasemi and Kazemi (2014) observed an increase in the susceptibility of L. monocytogenes subjected to the sublethal level of the environmental stresses (HCl, pH = 5.0) with a decreased MIC for gentamicin and rifampicin [73]. For A. baumannii, Ebinesh et al (2018) tested the influence of pH stress (acid at 3, 5, and 6 and alkaline at 9 and 10 pH for 2 h) on the antibiotic susceptibility of six strains; the exposure to acidity conferred a higher degree of resistance than alkalinity to amikacin, piperacillin, tazobactam, imipenem and meropenem.…”
Section: Food Preservatives and Decontaminantsmentioning
confidence: 92%
“…Exposure to environmental stress influences cell morphology, antimicrobial resistance (AMR), pathogenicity and virulence of L. monocytogenes through the expression of a number of genes ( Matereke and Okoh, 2020 ). More, sublethal stress may contribute to stress adaptation (resistance to higher levels of the same stress factor) or cross-resistance (resistance to other stress factors) ( Faezi-Ghasemi and Kazemi, 2015 ). The pathogen has developed a number of mechanisms that allow adaptation to stressful conditions.…”
Section: Pathogenicity and Adaptation To Stress Conditionsmentioning
confidence: 99%
“…According to the crystal structure, the LLO consists of four distinct domains (D1—D4), which play a different role in the functioning of the LLO ( Köster et al, 2014 ). The D1 domain possesses a structural motif in the C-terminal region, crucial for membrane binding and the cytotoxic activity of the LLO ( Faezi-Ghasemi and Kazemi, 2015 ; Materake and Okoh, 2020 ). In turn, the D2 domain is the sequence that joins D1 to D4 via a glycine linker ( Rosado et al, 2008 ; Köster et al, 2014 ).…”
Section: Patgogenicity Islandsmentioning
confidence: 99%